An assessment of policies affecting Sustainable Soil Management in Europe and selected member states. (July 2017) - Turpin, Nadine; ten Berge, Hein; Grignani, Carlo; Guzmán, Gema; Vanderlinden, Karl; Steinmann, Horst-Henning; Siebielec, Grzegorz; Spiegel, Adelheid; Perret, Eric; Ruysschaert, Greet; Laguna, Ana; Giráldez, Juan Vicente; et al.
Abstract: This paper analyses soils-related policies in Europe and in selected member states and regions. Our approach breaks down policy packages at European, national and regional levels into strategic objectives, operational objectives, policy measures and expected impacts, and assesses the relationships between these elements and soil stakes. Four major policy packages, both at EU and national level (CAP-I, RDP, Environment, national initiatives) were analysed. A numerical scale was developed to quantify the level of "embeddedness" of soil stakes in these policy packages. We found that countries better embed soil stakes into their policies when they also put more efforts on environmental innovation. In turn, countries with a high embeddedness level, with high trust in European institutions and that make more efforts towards renewable energy, tend to propose a wider variety of management practices to farmers for dealing with soil stakes.